Aspirin vs. P2Y12 inhibitors with anticoagulation therapy for atrial fibrillation: insights from the AFIRE trial. (14th October 2021) - Fukaya, H; Ako, J; Yasuda, S; Kaikita, K; Akao, M; Matoba, T; Nakamura, M; Miyauchi, K; Hagiwara, N; Kimura, K; Hirayama, A; Matsui, K; et al.
Abstract: Background: Patients with coronary artery disease (CAD) and atrial fibrillation (AF) can be treated with multiple antithrombotic therapies including antiplatelets and oral anticoagulants; however, this has the potential to increase bleeding risk. Purpose: This sub-analysis aimed to evaluate the efficacy and safety of P2Y12 inhibitors and aspirin in patients also receiving oral anticoagulant therapy. Methods: We evaluated patients from the Atrial Fibrillation and Ischemic Events with Rivaroxaban in Patients with Stable Coronary Artery Disease (AFIRE) trial who received combination therapy (rivaroxaban plus a single antiplatelet agent). The choice of antiplatelets was left to the physician's discretion. The primary efficacy endpoint was a composite of stroke, systemic embolism, myocardial infarction, unstable angina requiring revascularization, and death from any cause. The primary safety endpoint was major bleeding according to the International Society on Thrombosis and Haemostasis criteria. Results: A total of 1, 075 patients were included (P2Y12 inhibitor group, n=297; aspirin group, n=778). Approximately 60% of patients were administered proton pump inhibitors (PPIs), and there was no significant difference in PPI use in the P2Y12 inhibitor and aspirin groups. Regarding the primary efficacy endpoint, there was no significant difference between the P2Y12 inhibitor and aspirin groups (hazard ratio, 1.31; 95% confidence interval, 0.88–1.94; p=0.178). Likewise, the primary safety endpoint was not different between the groups (hazard ratio, 0.79; 95% confidence interval, 0.43–1.47; p=0.456). In the detailed subgroup analysis, there were no differences in the efficacy and safety endpoints. Conclusions: There were no significant differences between P2Y12 inhibitors and aspirin in cardiovascular events in patients with AF and stable CAD taking rivaroxaban in the chronic phase. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Japan Cardiovascular Research Foundation based on a contract with Bayer Yakuhin, Ltd.